Does Having a Smoking Friend or Parent Encourage Baghdad Medical Students to Smoke - Majeed, Saba Hameed; Murtadha, Mohammed; Alcharrakh, Ahmed Mohammed Ahmed (Journal of Pharmacology and Drug Development, 2025)
Objective: worldwide to lessen the impact of the tobacco pandemic. A major roadblock to reducing tobacco consumption is the absence of smoking statistics in the Iraqi population. The study set out to answer the question, " Does having a smoking friend or parent encourage Baghdad Medical students to smoke?" by looking for a correlation between social contacts and smoking behaviors within the demographic and the prevalence of smoking among medical students. Methods: This work uses cross-sectional studies to investigate the effects of social and familial elements as well as their consequences for public health policies. Students’ one-on-one encounters in healthcare environments provided the data for the cross-sectional observational study. Comprising 599 college students ranging in age from 18 to 23, the sample included two groups of smoking and nonsmoking individuals. Conclusions: This study intends to investigate how friends and parents’ behavior affect medical students from Baghdad’s smoking behavior. The data showed a significant relationship among the smoking group who already had a parent or a friend who smokes. The study recommends a new anti-smoking campaign focused on the medical students. Stressing the need for robust and resilient training and awareness efforts to reduce this phenomenon.